2019
DOI: 10.1111/nep.13571
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance spectroscopy‐guided fluid management in peritoneal dialysis patients with residual kidney function: A randomized controlled trial

Abstract: Aim Bioimpedance spectroscopy (BIS) allows volume status to be assessed objectively. This study evaluated the effect of BIS‐guided fluid management on residual kidney function (RKF), volume status, and cardiovascular events in peritoneal dialysis (PD) patients. Methods A multicenter, prospective, randomized, controlled trial was conducted over 12 months in 2013–2017. Non‐anuric PD patients (urine volume ≥ 500 mL/day) were randomized to clinical method‐guided management (n = 98) or BIS‐guided management (n = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Our previous investigation of the relationship between overhydration and residual kidney function (RKF) demonstrated that overhydration could lead to a decline in RKF per se (30). A recent study from Korea showed that BIA-guided fluid control did not affect RKF of patients on PD (31). In our cohort, the baseline median urine volume was only 250 ml and 88 (36%) patients had anuria.…”
Section: Discussionmentioning
confidence: 56%
“…Our previous investigation of the relationship between overhydration and residual kidney function (RKF) demonstrated that overhydration could lead to a decline in RKF per se (30). A recent study from Korea showed that BIA-guided fluid control did not affect RKF of patients on PD (31). In our cohort, the baseline median urine volume was only 250 ml and 88 (36%) patients had anuria.…”
Section: Discussionmentioning
confidence: 56%
“…For example, in dialysis trials, bioimpedance-based assessment of fluid status versus standard clinical assessment improved parameters such as blood pressure, left ventricular mass and arterial stiffness (25,(76)(77)(78). This is yet to be shown to impact upon risk of hard clinical outcomes: randomized trials comparing bioimpedance added to standard care versus standard of care alone have not demonstrated meaningful impact on hospitalizations (32,78), preservation of residual kidney function (79,80), cardiovascular outcomes or death (32,77,78,81,82), but numbers of outcomes in completed trials are generally small (83). Existing national clinical guidelines support the use of bioimpedance devices in dialysis patients when clinical assessment is challenging and suggest further consideration of the role of devices (84, 85) though cost-effectiveness must be considered and has not yet been demonstrated (25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no added benefit was demonstrated with regard to cardiovascular event-free or anuria event-free survival between the 2 methods (log-rank p 0.161 and 0.933, respectively) [88]. Similarly, results of another Korean RCT showed that BIS-guided fluid management had no effect on RRF, BP levels, echocardiographic parameters, and CV event rates [89]. In another RCT, 308 PD patients were recruited in 4 groups, according to their country of origin (UK or China) and status of RRF (anuric or nonanuric) to account for different therapeutic options available and anthropometric characteristics, as well as the effect of remaining kidney function.…”
Section: Bia Techniquesmentioning
confidence: 99%